Exploring artistic abilities and creativity perceptions for the enrolled architectural engineering students - Alnema, Mazin Jaber Omar; Dabdoob, Rawia Marwan (Periodicals of Engineering and Natural Sciences (PEN), 2022)
Architecture is considered one of the most significant human arts aims creativity in design. Therefore, it requires certain artistic skills and certain knowledge and perception from students. Architects are expected to have graphical communication skills enable them to translate their thoughts and ideas to sketching, drawing, model making, coloring, and rendering. The staff of first stage noticed the inadequate level of knowledge and shortfall in students’ abilities throughout years of education. Therefore, this paper aims to explore artistic abilities and creativity perceptions for the enrolled architectural engineering students. The research focuses on the first-grade students in Architectural Engineering Departments of University of Mosul. Mixed approaches were adopted for data collection including two surveys and ten in-depth interviews with the students after one month from their enrollment in university. The survey includes 68 questions serve four main axes, particularly, explores personal characteristics and abilities, traces students’ knowledge, investigates students’ artistic abilities and creativity perceptions, and tackles the role of school in developing artistic abilities and creativity for students. Findings reveal lack of student’s experience in artistic skills including sketching, drawing, or coloring, basic knowing about international or local architecture. This low qualification refers to underestimate art subject and lack of basic knowledge of architecture gained during students’ secondary education.